Fish identification in the Putus Lake, Pangkalan Baru Village, Siak Hulu District, Kampar Regency, RiauProvince - Pradita, Yuni; Windarti, Windarti; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractPutus lake is an oxbow lake that receive water from the Kampar River during the rainy season. This lake is inhabited by many fish species, however, the information on the type of fish in that area is limited. A study aims to understand the identification of freshwater fish in the Putus Oxbow Lake has been done from January to February 2020. Fish sampling were conducted every day for two weeks or there is no new species found. The fishes were captured using lures, gill nets and bamboo traps. Fish samples were then identified. Results shown that the caught fish consists of 3 orders, 12 families, 20 genera and 22 species. They were Cryptopterus bichirchis, Thynnichthys thynoides, Puntius bula, Oxygaster anomarula, Puntius schwanefeldii, Rasbora cephalotaenia, Helestoma temminckii, Channa syriata, Notopterus boorneensis, Peristolepis grooti, Amblyrhynhicthys truncatus, Cyhclocheilichthys apogon, Barbichthys laevis, Oxyeleotris marmorata, Mystus nemurus, Trichogaster pectoralis, Clarias batrachus, Pangasius polyuranodon, Osteochilus hasselti, Channa lucius, Mystus nigriceps, dan Mastacembelus unicolor. Among 22 species captured, 12 species were edible fishes, and 10 species were ornamental- edible fishes. The water quality of the lake were as follows: temperature of 29-30oC, brightness of 44-66 cm, pH 5, dissolved oxygen4.2-5.2 mg/L andcarbondioxide4.99-7.99 mg/L.Keywords :Oxbow lake, freshwater fish ,edible fishes, Cryptopterus bichirchis